Digital Da'wah Content in Islamic Religious Education: Critical Reception and Curriculum Integration in Banten Senior High Schools - Fatmawati Fatmawati; Umi Musyarofah; Kalsum Minangsih (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study examines digital da'wah content, namely religious lectures by Islamic scholars on YouTube and Instagram, as a supplementary learning resource in Islamic Religious Education (PAI) in public senior high schools in Banten Province, Indonesia. Adolescent Muslim consumption of such content has grown substantially, yet the formal PAI curriculum has not responded to it pedagogically. The study maps students' consumption patterns, analyses their critical reception capacity, and identifies opportunities and constraints for integration within the Merdeka Curriculum. A sequential explanatory mixed-methods design was used: a survey of 324 students from six public senior high schools, followed by phenomenological interviews with 24 students. Quantitative data were analysed with Structural Equation Modeling using Partial Least Squares (PLS-SEM) in SmartPLS 4.0, and qualitative data through inductive thematic analysis grounded in Freire's critical awareness framework. Findings show that 78.4 percent of students actively consume digital da'wah content, yet only 31.2 percent demonstrate adequate source verification capacity. Such content significantly influences religious identity formation (b = 0.412; p < 0.001; R² = 0.341). Students with stronger critical reception show more internalised religious motivation, indicating that reception quality, not consumption volume, drives identity outcomes. The study proposes a three-tier integration model covering Islamic-media critical literacy, a da'wah content curation guide, and digital-literacy competency training for teachers.